Efektivitas Penggunaan Media Peta Interaktif Untuk Meningkatkan Pemahaman Materi Geografi Pada Siswa Sekolah Dasar - Adi Sofyan Firmansyah; Lanlan Muhria; Muhammad Abdul Gani (Yayasan Satya Daya Insani, 2026)
Abstract This research aims to analyze the effectiveness of using interactive map media in improving elementary school students' understanding of geography material. The method used is descriptive qualitative with a literature study, utilizing various recent sources from both national and international journals. The study results indicate that interactive map media, such as digital maps based on Google Earth and geographical learning applications, have a positive influence on students' understanding of spatial concepts, geographical location, and natural phenomena (Prastya & Maharani, 2023; Ramadhani & Kurnianto, 2025). Furthermore, these findings confirm that technology-based social studies learning can enhance students' learning motivation and spatial thinking skills, aligning with the research results of Dewi et al. (2024) and Novitasari & Miaz (2023), who emphasize that interactive visual media helps facilitate the understanding of abstract concepts. Critical analysis also shows that the use of digital maps can bridge the gap between theory and the geographical reality students face daily, as stated by Maulaya et al. (2025). Thus, the use of interactive map media is not only theoretically relevant but also has practical implications for improving the quality of social studies learning in elementary schools. This research recommends that teachers integrate interactive map technology with the curriculum to create educational, participatory, and contextual learning. Keywords : Interactive map media, geographical material, elementary school.